2013
DOI: 10.1371/journal.pone.0060349
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Textured Material in Supporting Perceptual-Motor Functions

Abstract: Simple deformation of the skin surface with textured materials can improve human perceptual-motor performance. The implications of these findings are inexpensive, adaptable and easily integrated clothing, equipment and tools for improving perceptual-motor functionality. However, some clarification is needed because mixed results have been reported in the literature, highlighting positive, absent and/or negative effects of added texture on measures of perceptual-motor performance. Therefore the aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 72 publications
(496 reference statements)
0
37
0
Order By: Relevance
“…In a recent review, Orth et al (2013) concluded that adding texture to the plantar surface of the feet via textured insoles or surfaces improves perceptual-motor performance (see also Palluel et al, 2008). For example, improvements in the postural sway of older adults when standing on textured insoles were reported by Qui et al (2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Orth et al (2013) concluded that adding texture to the plantar surface of the feet via textured insoles or surfaces improves perceptual-motor performance (see also Palluel et al, 2008). For example, improvements in the postural sway of older adults when standing on textured insoles were reported by Qui et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Waddington and Adams (2003) demonstrated that male soccer players exhibited better discrimination between different extents of subtalar inversion when a textured insole was placed in their shoe. In a recent systematic review, Orth et al (2013) concluded that there is clear support for using textured materials to improve perceptual-motor performance. For example, textured insoles have been shown to decrease postural sway, and enhance balance, in older people (Qiu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For dependent group designs, effect size estimates for lower-limb stimulation strategies for the control group in each study were standardized using the control group standard deviation value [12]. However, the pooled standard deviation was used as the denominator in independent group designs [51].…”
Section: Methodsmentioning
confidence: 99%
“…To date, systematic reviews have tended to only focus on a single stimulation strategy such as the role of textured materials [12], shoes and ankle appliances [3] and ankle taping and bracing [13]. Two of these studies quantified the review in a meta-analysis [12,13]. These studies have provided an overview of the effects of specific lower-limb stimulation strategies on balance control, but have been limited in not comparing the relevance of different stimulation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the textured insoles have also been considered in improvement of sensation status of plantar surface [20] or ankle injuries [21]. The use of textured insoles is based on the assumption that it changes the discharge rate of the mechanical receptors [19,22,23]. In addition, based on the theory of sensory reweighting, enhancement of sending data via mechanoreceptors may somewhat offset the inadequacy of other sources of balance [21,24,25].…”
Section: Crossmarkmentioning
confidence: 99%